2018
DOI: 10.1152/advan.00181.2017
|View full text |Cite
|
Sign up to set email alerts
|

Detrended fluctuation analysis in a simple spreadsheet as a tool for teaching fractal physiology

Abstract: Fractal physiology demonstrated growing interest over the last decades among physiologists, neuroscientists, and clinicians. Many physiological systems coordinate themselves for reducing variability and maintain a steady state. When recorded over time, the output signal exhibits small fluctuations around a stable value. It is becoming increasingly clear that these fluctuations, in most free-running healthy systems, are not simply due to uncorrelated random errors and possess interesting properties, one of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Furthermore, the recent introduction of DFA technique for heart rate variability measuring appears to provide improved prognostic methods of cardiovascular diseases diagnostics by calculating the alpha fractal scaling component (Willson et al, 2002; Chiang et al, 2016). As it was noted by Arsac and Deschodt-Arsac (2018), in the last decade there has been a growing interest in fractal physiology among neuroscientists and clinicians. Many physiological systems coordinate themselves to reduce variability and maintain a steady-state.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the recent introduction of DFA technique for heart rate variability measuring appears to provide improved prognostic methods of cardiovascular diseases diagnostics by calculating the alpha fractal scaling component (Willson et al, 2002; Chiang et al, 2016). As it was noted by Arsac and Deschodt-Arsac (2018), in the last decade there has been a growing interest in fractal physiology among neuroscientists and clinicians. Many physiological systems coordinate themselves to reduce variability and maintain a steady-state.…”
Section: Discussionmentioning
confidence: 90%
“…Al-Angari and Sahakian ( 2007) study also found a significant reduction in SampEn in patients with OSA, supporting the notion that these patients have a more predictable heart rate oscillation. Altogether, those findings with DFA and entropy indicate that patients with OSA have altered fractal dynamics and decreased unpredictability of heart rate oscillations, a condition consistent with loss of physiological complexity in patients with OSA (Goldberger et al, 2002;Burggren and Monticino, 2005;Porta et al, 2007a;Arsac and Deschodt-Arsac, 2018). Although none of the asymmetry indices were found different among groups, the acceleration capacity is decreased in patients with moderate OSA.…”
Section: Hrv Analysis Between Normal and Osa Individualsmentioning
confidence: 68%
“…After artifact correction, a series of 256 R-R intervals was retained for each participant under each experimental condition for subsequent analyses, in accordance with previous guidelines ( Shaffer and Ginsberg, 2017 ) and in order to have the same number of intervals for each subject ( Ribeiro et al, 2018 ). Series of R-R intervals were linearly detrended before evaluating their complexity, in accordance with standard methodology ( Peng et al, 1995 ; Delignières et al, 2005 ; Arsac and Deschodt-Arsac, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…DFA was used because it provides reliable results for “short” time series, especially for 256 data ( Almurad and Delignières, 2016 ; Liddy and Haddad, 2018 ). The DFA methodology was previously described ( Delignières et al, 2005 ; Almurad and Delignières, 2016 ; Arsac and Deschodt-Arsac, 2018 ; Liddy and Haddad, 2018 ). To sum up, DFA analyses the relationship between the average fluctuation amplitude and the size of the observation window where these fluctuations are measured.…”
Section: Methodsmentioning
confidence: 99%